2019
DOI: 10.17235/reed.2019.5819/2018
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and impact of portal vein thrombosis in liver transplantation

Abstract: Introduction: portal vein thrombosis is a relatively common complication of advanced cirrhosis that increases perioperative risk in liver transplant recipients. This condition was characterized in a cohort of patients, including risk factors and their influence on survival. Material and methods: a retrospective study of liver transplant recipients at the Clínica Universidad de Navarra was performed between 2000 and 2015. Differences in clinical and biological characteristics and survival were analyzed in subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, a follow-up study of 6708 subjects in Norway showed that waist circumference is the best anthropometric indicator for obesity and can predict the risk of venous thromboembolism [ 37 ]. Several studies have shown that obesity is an independent risk factor associated with PVT in patients with cirrhosis after liver transplantation [ 38 , 39 ]. Similarly, a study in France showed that central obesity may be the primary risk factor of noncirrhotic PVT [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a follow-up study of 6708 subjects in Norway showed that waist circumference is the best anthropometric indicator for obesity and can predict the risk of venous thromboembolism [ 37 ]. Several studies have shown that obesity is an independent risk factor associated with PVT in patients with cirrhosis after liver transplantation [ 38 , 39 ]. Similarly, a study in France showed that central obesity may be the primary risk factor of noncirrhotic PVT [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another independent risk factor for PVT is the degree of thrombocytopenia, and this is also emphasized in the Baveno VII consensus report as patients with low platelet counts are at a higher risk of PVT. [ 9 , 22 , 23 ] This seems paradoxical since a low platelet count should logically predispose to bleeding. As cirrhosis and portal hypertension progress, the resultant decrease in portal flow outweighs the protective effect of low platelet count against thrombosis, and the paradoxical finding of increased PVT with lower platelet counts may thus be related to decreased portal flows that occur with the progression of portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of data suggests that an association between PVT development and esophageal varices. The presence of esophageal varices is significantly correlated with a higher rate of PVT, demonstrating esophageal varices may be an important part evaluating the risk of PVT (25)(26)(27). In this study, esophageal varices was identified as a significant PVT predictor in cirrhotic patients.…”
Section: Figurementioning
confidence: 99%